Fibrinogen storage disease and cirrhosis associated with hypobetalipoproteinemia owing to fibrinogen Aguadilla in a Turkish child. (18th August 2015) - Sari, Sinan; Yilmaz, Guldal; Gonul, Ipek I.; Dalgic, Buket; Akyol, Gulen; Giovannoni, Isabella; Francalanci, Paola; Callea, Francesco
Abstract: Background and Aims: Fibrinogen gene mutations can rarely result in hepatic fibrinogen storage disease (HFSD). Herein, we report on the first Turkish family carrying the mutation p.Arg375Trp (fibrinogen Aguadilla) in the γ‐chain of the fibrinogen ( FGG ) gene. Methods: Clinical, laboratory and histopathological findings of the patient were documented. Molecular study of fibrinogen gene was performed in the patient and her family members. Results: The proband was 5 years old girl presenting with advanced liver fibrosis of unknown origin. The child had very low plasma levels of fibrinogen and hypobetalipoproteinemia. Immunomorphologic and electron microscopic studies showed selective and exclusive accumulation of fibrinogen within the endoplasmic reticulum in liver biopsy of the patient. Patient, mother, two sisters and one brother carried p.Arg375Trp mutation (fibrinogen Aguadilla) in FGG gene. The patient was treated with ursodeoxycholic acid and carbamazepine. After 3 months, carbamazepine was suspended upon family decision and unresponsiveness of carbamazepine. Conclusions: HFSD is characterized by hypofibrinogenemia and accumulation of abnormal fibrinogen within hepatocytes. In addition, hypofibrinogenemia is associated with hypobetalipoproteinemia in Aguadilla mutation.